2019
DOI: 10.1186/s12889-019-7645-9
|View full text |Cite
|
Sign up to set email alerts
|

Trends in overweight and obesity by socioeconomic status in Year 6 school children, Australian Capital Territory, 2006–2018

Abstract: BackgroundDue to the high prevalence and adverse consequences, overweight and obesity in children continues to be a major public health concern worldwide. Socioeconomic background and health-related behaviours (such as diet, physical activity and sedentary behaviors) are important factors associated with weight status in children. Using a series of height and weight assessments from the Australian Capital Territory Physical Activity and Nutrition Survey (ACTPANS), trends in prevalence of overweight and obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 45 publications
5
29
1
1
Order By: Relevance
“…The differences in the age at which these inequalities emerged might support the evidence that early life factors such as breast feeding, smoking during pregnancy, dietary and physical activity behaviours, which affect BMI, have different socioeconomic patterns in different countries [41][42] . Our study results indicated that Norwegian children showed the same pattern of socioeconomic inequalities in OW/OB trajectories as other high-income countries showing a higher proportion of childhood OW/OB among the lower socioeconomic groups 43,44 , which is in accordance with the reversal hypothesis 45 .…”
Section: Discussionsupporting
confidence: 84%
“…The differences in the age at which these inequalities emerged might support the evidence that early life factors such as breast feeding, smoking during pregnancy, dietary and physical activity behaviours, which affect BMI, have different socioeconomic patterns in different countries [41][42] . Our study results indicated that Norwegian children showed the same pattern of socioeconomic inequalities in OW/OB trajectories as other high-income countries showing a higher proportion of childhood OW/OB among the lower socioeconomic groups 43,44 , which is in accordance with the reversal hypothesis 45 .…”
Section: Discussionsupporting
confidence: 84%
“…For example, some literature has suggested that the patterning of childhood obesity according to certain risk factors, such as ethnicity or socioeconomic status, may differ for males and females. 32 33 In this case, it would be important to both report overall prevalence of obesity and also analyse the sociodemographic patterning of obesity separately for boys and girls. Of the studies that have investigated differences, most focus on biological sex (male vs female) only.…”
Section: Applying Sex-based and Gender-based Analysis To Childhood Obmentioning
confidence: 99%
“…It should be emphasized that the association between overweight and breakfast skipping could not be explained by the most common predictors of overweight, SES, and parental overweight [11,52,53]. Therefore, interventions targeting breakfast behavior provide a suitable starting point for weight gain interventions even more because breakfast can be integrated into the school day-and is therefore independent of the child s social background.…”
Section: Association Of Breakfast and Lunch Behavior With Overweightmentioning
confidence: 99%